التفسير من التأسيس إلى المعاصرة: Quranic Exegesis from Its Beginning to the Contemporary - Naser Almulla, Abdullah Sabah (Online Journal of Research in Islamic Studies, 2021)
This study provides the definition of tafsir (interpretation of the Qur’an) both in term and language, some basic background of it's history and the precession after that. The history starts from the early days of the Prophet Muhammad (PBUH), continued by the companions (May Allah be pleased with them) and then by the successors until our modern time today. This study also explains the tools to interpret Qur’an; by means of the Qur’an, then by the means of hadith and then by what was transmitted by the Companions (God be pleased with them), and then by the words of the righteous successors. More than that, the excegitation (Istinbat), independent reasoning (Ijtihad) and the early learning-center of tafsir are mentioned too. Not to be forgotten, the student collects some narration and statement of the Islamic scholars and their argument in this field. Besides that, he shortlists some of the famous books of tafsir - both classical and contemporary - which is a must for a student of knowledge, following the study-method.